PENGARUH SISTEM INFORMASI AKUNTANSI PRODUKSI TERHADAP AKTIVITAS PRODUKSI PADA PT. HILON - Oktapiandi, Deni; Suantha, Kasan K. (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to analyze the impact of the production accounting information system on production activities at PT. Hilon. The production accounting information system plays a significant role in improving the efficiency and effectiveness of manufacturing operations by providing accurate information regarding production costs, inventory control, and workforce and machinery optimization. The research method used is a quantitative approach with a survey method, where data was collected through questionnaires distributed to accounting managers and production-related employees. Data analysis was carried out using validity tests, reliability tests, and Pearson Product Moment correlation analysis. The results indicate that the production accounting information system has a significant relationship with various aspects of production activities, including product design, production planning and control, production operations, and cost accounting. The correlations found range from moderate to strong, indicating that the optimal implementation of the production accounting information system can enhance production process efficiency. Therefore, PT. Hilon is advised to continuously develop its production accounting information system to improve its competitiveness in the manufacturing industry.